Performing a metamorphosis: a teaching performer or performing teacher? - Stanberg, A.; Bennett, Dawn (Guildhall School of Music and Drama, London, 2006)
The notion of a teaching artist has gained considerable popularity amongst freelance musicians seeking increased employment and performance experiences. This paper presents findings from the first phase of a longitudinal study which explored a shift in identity from performer to teacher as a professional percussionist retrained to become a classroom music teacher. Aiming to identify the effect that formal teacher training had upon the teaching artist, the study considered: 1) the inter-relationships between teaching and performance roles; 2) the rationale for a change in role; and 3) the balance between the two identities. Using a case study approach, the study comprised of interviews and observation of teaching practice. The participant demonstrated characteristics typical of a career change such as a desire to maintain more regular hours and income, and also a positive rationale for adopting a teaching role following positive teaching artist encounters. Findings emphasise the need for educators to be conversant with the emotional and educational needs of the growing numbers of performers who undertake teacher training so that teacher identity can develop through positive interactions with teaching and communicating music.